Profiling of bovine toll like receptors (TLRs) in foot and mouth disease vaccinated cattle - RANJAN, RAJEEV; BISWAL, JITENDRA KUMAR; SHARMA, AJAY KUMAR; MISRI, JYOTI; PATTNAIK, BRAMHADEV (The Indian Journal of Animal Sciences, 2016)
Foot and mouth disease virus (FMDV) elicits acute humoral antibody response in both infected and vaccinated animals. Toll like receptors (TLRs) are type 1 transmembrane proteins expressed in almost all cell types and activate the innate immune system. The current study was performed to evaluate expression profiling of bovine TLRs like TLR 2, TLR 3, TLR 7, TLR 8 and TLR 10, in response to FMD inactivated vaccine using quantitative real-time RT-PCR technique. Blood samples were collected from control, test group 1 and test group 2, at 0, 14th and 21st days post-vaccination (dpv). The mRNA abundance of these target genes was calibrated with a housekeeping gene (18 S) and expressed as fold over expression of the TLRs genes in bovine over the 0th dpv as control. On 0 day, expression of all TLRs did not vary significantly. The expression of TLR2 and TLR3 genes significantly increased in both test group 1 and 2 after 14th day and 21st DPV but expression of other TLRs increase in test groups 1 and 2 did not differ significantly. Expression of TLR2 and TLR3 genes considerably increased in test group 1 and 2 but expression of these genes were more in test group 1 as compared to test group 2. From preliminary findings, if there is inclusion of TLR2 and TLR 3 agonist in vaccine, it may enhance the innate immunity of animals and helps in clearing of virus and may prevent establishment of infection.